Concomitant herpes simplex keratitis and autoimmune-associated ulcerative keratitis in rheumatoid arthritis patients - Yoshida, Masaaki (Am J Ophthalmol Case Rep, 2020)
PURPOSE: To describe four cases of concomitant herpes simplex keratitis (HSK) and autoimmune-associated ulcerative keratitis (UK) in patients with rheumatoid arthritis (RA). OBSERVATIONS: All patients developed HSK and UK while undergoing treatment for RA. The average age of onset for RA, UK and HSK was 49.3, 69.5 and 70.5 years, respectively. UK preceded HSK in three cases and followed HSK in one case. Two patients had bilateral UK and two had unilateral UK. HSK was unilateral in all cases. All the cases had been treated with immunosuppressive agents including steroid, methotrexate, calcineurin inhibitors, etanercept and tocilizumab at the onset of HSK. Every patient was treated for HSK with topical acyclovir ointment combined with oral valacyclovir. The final visual outcome was extremely poor despite intensive therapy. CONCLUSIONS AND IMPORTANCE: These cases raise the possibility that RA patients have an increased risk of HSK, and that HSK may tend to be severe in these patients because of their immunocompromised condition. Furthermore, the complication of HSK and UK in RA patients is difficult to treat because of the atypical clinical manifestation. Thus, the emergence of corneal ulcer, especially in patients with a long clinical history of RA, calls for careful follow-up.